Pengaruh Behavioral Relaxation Training terhadap Nyeri Kanulasi (Av-Shunt) pada Pasien Ginjal Kronik yang Menjalani Hemodialisis di Rumah Sakit TK.II Dr. Soedjono Magelang - Endro Haksara; Ainnur Rahmanti; Dian Pratama; Yesi Puspitasari (Jurnal Kesehatan Amanah, 2024)
Cannulation pain during hemodialysis procedures is a common complaint among patients with chronic kidney failure. Behavioral Relaxation Training (BRT) can be a non-pharmacological intervention to manage this pain. The objective of this study is to analyze the effect of BRT on cannulation pain levels in hemodialysis patients. Method: This study is quasi-experimental with a pre-post test design involving 60 patients divided into intervention and control groups. Pain measurement was performed using the Numerical Rating Scale (NRS). Results: Statistical tests showed a significant reduction in cannulation pain in the intervention group compared to the control group (p<0.05).Conclusion: Behavioral Relaxation Training is effective in reducing cannulation pain in chronic kidney failure patients undergoing hemodialysis.